menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Given the definitions of f ( x ) f(x) and g ( x ) g(x) below, find the value of f ( g ( − 1 ) ) . f(g(−1)). f ( x ) = f(x)= 4 x + 14 4x+14 g ( x ) = g(x)= 3 x 2 + 5 x − 6 3x 2 +5x−6
asked
Sep 9, 2023
68.1k
views
23
votes
Given the definitions of
f
(
x
)
f(x) and
g
(
x
)
g(x) below, find the value of
f
(
g
(
−
1
)
)
.
f(g(−1)).
f
(
x
)
=
f(x)=
4
x
+
14
4x+14
g
(
x
)
=
g(x)=
3
x
2
+
5
x
−
6
3x
2
+5x−6
Mathematics
high-school
Yesennes
asked
by
Yesennes
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
3
votes
Answer:
i dont know the question what does it mean
Explanation:
Godblessstrawberry
answered
Sep 14, 2023
by
Godblessstrawberry
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org